ISOLASI DAN SIFAT LIGNIN DARI LARUTAN SISA PEMASAK PABRIK PULP (Isolation and properties of lignin from black liquor of pulp industry) - Tjutju Nurhayati; Ridwan Ahmad Pasaribu (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
the study is aimed to find the isolation techniques and properties al lignin component of black Liquors from pulp industry.The samples were taken from Basuki Rahmat pulp industry, namely black liquor of sulfate pulping from evaporator (with pH 13. 52) and from digester (pH 10.58), and from Basuki Teguh, namely neutral sulfite semi chemical pulping (pH 6.85). The isolation was conducted by using two kinds of acid i.e. sulphuric acid 2 N and chloric 2 N each at pH 3. and pH 5.The result revealed that the yield and quality of lignin isolated at pH 2 was higher than other pH levels. At this pH level, the lignin produced from sulfate pulping black liquor of exporator was 21.04%, and from digester was 7.47 %, and of neutral sulfide semi chemical pulping was 0.57%. the lignin properties of each black liquor were as the following : pure lignin content was 70.41 %, 72. 55 % and 68. 29 % , respectively ; methoxyl content was 5. 62 %, 11.17 % and 8. 95 % respectively, and particle surface area was 33.87 m3/g, 29.81 m2/g and 28.03 m2/g, respectively,Different from other lignin properties, highest acidity and water absorption capacity of lignin was produced by one which was isolated by chloric acid at pH level 5. the water absorption capacity and lignin acidity of sulfate pulping black liquor of evaporator was 122.45% and pH 6; and of digester was 119. 17 % and pH 6.03; and of neutral sulfide semi chemical pulping was 116.60 % and pH 5.53.